Analysis of Factors Affecting Work Productivity of Tea Pickers at the Tea and Quinine Research Center, Simalungun Regency - Sagutray Simangunsong, Roki (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to determine the effect of age, work experience, and gender on the work productivity of tea pickers. This research was conducted in the PPTK Laut Tawar Gardens, Simalungun Regency. The sampling technique used is probability sampling technique with a sample size of 40 respondents. To determine the factors that influence the work productivity of tea pickers at the Tea and Quinine Research Center, Simalungun Regency, statistical analysis was used with the classical assumption test method, multiple linear, and hypothesis testing. Data processing using SPSS computer software. The results of this study indicate that all independent variables, namely age (X1), work experience (X2) and gender (D1) simultaneously, have a significant effect on the dependent variable, namely work productivity (Y).